Effects of ball milling on the structural, thermal, and rheological properties of oat bran protein flour - Ramadhan, Kurnia; Foster, Tim (Elsevier, 2018)
Oat bran protein flour (OBPF), containing protein, starch, and lipid as major constituents, was ball milled and subsequently evaluated on structural conformation, thermal properties, particle size distributions, and rheological properties. Prior to ball milling, characterisation of OBPF were conducted by means of Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) showing the existence of aggregated protein and starch-lipid complexes as predominant constituents of OBPF. Ball milling altered structural conformations of both protein and starch. Moreover, increase of ball milling time gradually decreased the transition enthalpy changes of amylose-lipid complexes upon heating which can be related to disruption of amylose-lipid complexes helical structure. Ball milling at higher speed resulted to smaller average particle size distributions of OBPF. Dynamic mechanical spectra of concentrated dispersions containing ball milled OBPF exhibited lower storage (G′) and loss (G″) moduli compared to control sample due to reduced particles volume packing. Moduli-frequency sweep data satisfactory fitted the Power Law’s model.